The Effects of Family Leave on Wages, Employment, and the Family Wage Gap: Distributional Implications - Jean Kimmel; Catalina Amuedo-Dorantes (Washington University Journal of Law & Policy, 2004)
Despite the proliferation of research and publications in recent years on the topic of the FMLA, little has been published to date presenting a broad overview of the economic impact of mandated family leave, particularly regarding its distributional effects for women and their children. We focus this Essay on the implications of family leave policy for wage gaps by motherhood status, as well as on the policy’s distributional effects. We begin by briefly describing the progress (and lack of progress) experienced by women in the workforce in the past half-century and discussing the factors thought to be important in these various outcomes. We then present the underlying economic theory of employer mandates, culminating with a discussion of the potential labor force impacts of mandated employer leave. Next, we use data from the 1979 National Longitudinal Survey of Youth to estimate the impact of state leave policies on employment and wage outcomes for women, both mothers and non-mothers, thereby producing estimates of such leave policies on the family earnings gap. Finally, we discuss distributional implications of the current FMLA policy and suggest policy revisions.
Keywords: Parental leave; Families; Employment